Baroclinic waves in an air-filled thermally driven rotating annulus - Castrejón Pita, A; Read, P (American Physical Society, 2007)
In this study an experimental investigation of baroclinic waves in air in a differentially heated rotating annulus is presented. Air has a Prandtl number of 0.707, which falls within a previously unexplored region of parameter space for baroclinic instability. The flow regimes encountered include steady waves, periodic amplitude vacillations, modulated amplitude vacillations, and either monochromatic or mixed wave number weak waves, the latter being characterized by having amplitudes less than 5% of the applied temperature contrast. The distribution of these flow regimes in parameter space are presented in a regime diagram. It was found that the progression of transitions between different regimes is, as predicted by recent numerical modeling results, in the opposite sense to that usually found in experiments with high Prandtl number liquids. No hysteresis in the flow type, with respect to variations in the rotation rate, was found in this investigation.